2003
DOI: 10.22621/cfn.v117i2.685
|View full text |Cite
|
Sign up to set email alerts
|

Space and Habitat Use by Male and Female Raccoons, <em>Procyon lotor</em>, in Kansas

Abstract: We monitored 12 radio-tagged adult Raccoons (Procyon lotor) from an unexploited population in northeastern Kansas to determine intersexual differences in space and habitat use. Home ranges (mean ± SE) of males were relatively large (266 ± 14 ha) and mutually exclusive, whereas home ranges of females were relatively small (122 ± 52 ha) and overlapped extensively. Sizes of home ranges were smaller (P < 0.05) in winter than summer for both sexes, although females reduced their home ranges more than males. Females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Conversely, space use was least during summer, a period when soft mast and invertebrates are abundant and relatively ubiquitous, allowing raccoons to fulfill energetic requirements without extensive movements. Previous research in northern latitudes has reported a reduction in winter space use, primarily attributed to raccoons reducing their activities during the coldest time periods (Stuewer, 1943;Glueck et al, 1988;Kamler and Gipson, 2003;Prange et al, 2004). This behavior is not typically observed in southern locations (Gehrt and Fritzell, 1997;Chamberlain et al, 2003;Fisher, 2007), presumably because the mild winters and lack of extreme temperature fluctuations maintain adequate food resources and allow raccoons to stay active during winter (Gehrt and Fritzell, 1997).…”
Section: Discussionmentioning
confidence: 96%
“…Conversely, space use was least during summer, a period when soft mast and invertebrates are abundant and relatively ubiquitous, allowing raccoons to fulfill energetic requirements without extensive movements. Previous research in northern latitudes has reported a reduction in winter space use, primarily attributed to raccoons reducing their activities during the coldest time periods (Stuewer, 1943;Glueck et al, 1988;Kamler and Gipson, 2003;Prange et al, 2004). This behavior is not typically observed in southern locations (Gehrt and Fritzell, 1997;Chamberlain et al, 2003;Fisher, 2007), presumably because the mild winters and lack of extreme temperature fluctuations maintain adequate food resources and allow raccoons to stay active during winter (Gehrt and Fritzell, 1997).…”
Section: Discussionmentioning
confidence: 96%
“…Most studies of spacing behavior and social interactions of raccoons have found that females are typically gregarious and socially tolerant of conspecifics (Gehrt and Fritzell 1998;Kamler and Gipson 2003;Walker and Sunquist 1997). However, no studies have examined in close detail the spatial organization of females in low-density portions of their distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Space use and social organization of the raccoon have been studied extensively in the southern portion of its distribution where population density is high (Zeveloff 2002). Raccoons have the ability to display a wide array of social tolerances, ranging from completely tolerant, to strict territoriality, to complex systems of associated and nonassociated aggregations (Chamberlain and Leopold 2002;Gehrt and Fritzell 1998;Kamler and Gipson 2003;Walker and Sunquist 1997). Ecological factors, such as dispersion of resources, may in part explain this variability observed across the species' distribution (Zeveloff 2002).…”
mentioning
confidence: 99%
“…The authors also suggested that the predictability of rabbit‐rich areas, as opposed to the less predictable nature of earthworm‐rich areas in the present study, may be of central importance to their observations, which they interpreted as within‐group resource competition. Differential habitat use between the sexes has been observed for other carnivores such as weasels Mustela erminea (Erlinge, 1979), fishers Martes pennanti (Kilpatrick & Rego, 1994), raccoons Procyon lotor (Fritzell, 1978; Kamler & Gipson, 2003) and grizzly bears Ursus arctos (McLoughlin et al , 2002). However, whether such behavioural differences underlie the relationships in the present study is unclear and is the subject of current research.…”
Section: Discussionmentioning
confidence: 99%